2014
DOI: 10.1016/j.molcel.2014.02.032
|View full text |Cite
|
Sign up to set email alerts
|

A Role for H3K4 Monomethylation in Gene Repression and Partitioning of Chromatin Readers

Abstract: Summary Mono-methylation of lysine 4 on histone H3 (H3K4me1) is a well-established feature of enhancers and promoters, although its function is unknown. Here, we reveal novel roles for H3K4me1 in diverse cell types. Remarkably, we find that MLL3/4 provokes mono-methylation of promoter regions and the conditional repression of muscle and inflammatory response genes in myoblasts. During myogenesis, muscle genes are activated, lose MLL3 occupancy, and become H3K4-trimethylated through an alternative COMPASS compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
198
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(234 citation statements)
references
References 43 publications
35
198
1
Order By: Relevance
“…These observations are consistent with recent studies showing that COMPASS-like MLL3/ MLL4 complexes predominantly monomethylate H3K4 at enhancer regions and specific promoter regions (Herz et al 2012;Hu et al 2013;Morgan and Shilatifard 2013;Cheng et al 2014). Interestingly, upon incubation of the MLL3 SET domain with the Ash2L/RbBP5 complex reconstituted with RbBP5 phos , peaks corresponding to H3K4me1 and H3K4me2 were observed.…”
Section: Rbbp5 Phosphorylation Controls Histone H3k4 Methylation By Ksupporting
confidence: 92%
See 1 more Smart Citation
“…These observations are consistent with recent studies showing that COMPASS-like MLL3/ MLL4 complexes predominantly monomethylate H3K4 at enhancer regions and specific promoter regions (Herz et al 2012;Hu et al 2013;Morgan and Shilatifard 2013;Cheng et al 2014). Interestingly, upon incubation of the MLL3 SET domain with the Ash2L/RbBP5 complex reconstituted with RbBP5 phos , peaks corresponding to H3K4me1 and H3K4me2 were observed.…”
Section: Rbbp5 Phosphorylation Controls Histone H3k4 Methylation By Ksupporting
confidence: 92%
“…MLL1/MLL2 di/trimethylate H3K4 (H3K4me2/3) and regulate Hox gene expression during embryonic development (Yu et al 1995;Dou et al 2006). MLL3/MLL4 regulate adipogenesis ) and primarily monomethylate H3K4 (H3K4me1) at both enhancer (Herz et al 2012;Hu et al 2013) and promoter (Cheng et al 2014) regions, while SET1A/B are the primary H3K4 trimethyltransferases (Wu et al 2008). However, despite divergence in catalytic activity and functional roles, enzymes of the KMT2/COMPASS family must assemble into multisubunit complexes to carry out their biological functions.…”
mentioning
confidence: 99%
“…Consistent with recent studies showing that MLL2 mutation affects H3K4 methylation at enhancers (Hu et al 2013;Lee et al 2013;Cheng et al 2014), we did detect potential mouse enhancers and other regulatory elements where H3K4 mono-and dimethylation in particular were affected (Supplemental Fig. S9C), but γH2AX-, RNA-PII-, and GRO-levels were not significantly affected in these locations (Supplemental Fig.…”
Section: Mll2 Mutation Affects Rnapii-associated Histone Methylation supporting
confidence: 91%
“…The closely related proteins MLL2 and MLL3 reside in nearly identical complexes, termed ASCOM (Lee et al 2009). Recent studies have provided evidence for a role for MLL2 and MLL3 in histone H3K4 methylation at enhancers (Hu et al 2013;Lee et al 2013;Cheng et al 2014), and it has thus been suggested that their role in cancer might be explained through deregulated expression of oncogenes and tumor suppressors (Herz et al 2014). However, the transcriptome of cells lacking MLL2 shows remarkably few differences from that of the wild-type counterpart, leaving few clues to explain tumorigenesis this way (Issaeva et al 2007;Guo et al 2012).…”
mentioning
confidence: 99%
“…H3K4me3 is enriched at transcriptional start sites from yeast to humans and is generally considered a mark of active or activated state of transcription (8,12). Although the role for H3K4me1 in Saccharomyces cerevisiae or the budding yeast is not yet known, it is present at "poised" developmental enhancers in embryonic stem cells (13) and implicated in gene repression in mammals (14). H3K4me2 and H3K4me3 are found predominantly at transcriptionally active loci (15)(16)(17), but recent studies in budding yeast have also linked these marks to transcriptional repression (9,18,19).…”
Section: Histone H3 Lysine 4 (H3k4) Methylation Is a Dynamic Modificamentioning
confidence: 99%